Opening Up and Geographic Diversification of Trade in Transition Economies - Havrylyshyn, Oleh (IMF Working Papers; Working Paper ;, 1998)
This paper looks at the progress in transition and the geographic diversification of trade, focusing on two issues--the degree of trade openness and trade integration--for a sample of countries in transition. It concludes that about half of the group of countries sampled are becoming as open as similar market economies, but that many others remain relatively closed. Geographic diversification (to the European Union) is found to be greater the closer is geographic proximity and the more advanced the country is with reforms. The analysis is then extended, in an illustrative way, to show how much larger would be the share of exports to the EU if structural reforms were more ambitious.